Pembinaan Metode Dirosa Pada Masyarakat di Masjid Al-Mujahidin Desa Malimongeng Kec. Salomekko Kab. Bone - Jukarlianto (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2023)
The purpose of this writer is to learn about how the dirosa method is used to read the Koran to the people of Malimongeng Village, Kec. Kab Salomekko Bone and to learn about the Malimongeng Village KKNP students' efforts to improve the community of Malimongeng Village, Kec,'s ability to read the Koran using the dirosa method. Salomekko Kab. Bone. A qualitative research method is used as the research approach, and it includes the following components: Data Sources, Data Collection Techniques, Data Analysis Techniques, Validity Data Checking, and Research Stages are all components of the research approach and design. Keywords: Dirosa's Development of Community